Assessing the Design and Implementation of English Training Program for the University of Surabaya Administrative Staff - Besin Gaspar; Yenny Hartanto (Soshum: Jurnal Sosial dan Humaniora, 2019)
This research aims at portraying the process of the design and implementation of the English training program for the administrative of University of Surabaya which was conducted from March to August 2017 by the Directorate of HRD and Language Center, University of Surabaya. It was intended to identify how the course was designed, implemented, evaluated and finally to judge to what extent the program was successful. The output of the research was a report to the university, especially HRD Directorate, giving evaluations and recommendations for the future similar training program. The data were collected using document studies, questionnaires and interviews. Using the principles of ADDIE design model, all the steps were evaluated: needs analysis, instructional design and development, implementation and evaluation/test instrument. The results of the analysis showed that the steps of the design was already in line with the ADDIE model design proposed by Reiser dan Mollenda in the (1990) but it failed to measure the gain or the increase in the competence level of the participants since the test instrument used in the pretest was TOEIC test, different from the one used in the posttest, that is, oral interview test designed by the teaching staff themselves. Therefore, the result could not be compared to see the gain. Seen from the participant satisfaction with the implementation and methods of delivery, the program was successful since the level of satisfaction was above 80 % ( above the target).Based on the findings, it is recommended that future training program improve the test instrument for the pretest and posttest in such a way that the gain is easier to measure